Formation of Research Competence of Future Economists in the Process of Mastering Foreign Languages - ALEKSANDROVA, Nataliya N.; SLUCHAYNA, Larysa (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018, 2019)
The relevance of the work is determined by the fact that the research competence of students of economic specialties is defined not only as the independence of communicative behavior but also as a product of modern pedagogical technologies. The subject of the work is research competence, which is formed, restructured and perfected in modern synergetic educational process. The novelty of the study is that research competence is interpreted not only as the ability to conduct an independent scientific research and provide its results. The prospect of further study is the possibility of correlating the above-mentioned approach to global educational standards.